Right and left prefrontal transcranial magnetic stimulation at 1 Hz does not affect mood in healthy volunteers - Lappin Julia M; Jenkins Jenny; Shajahan Polash M; Ebmeier Klaus P (BMC Psychiatry, 2002)
Abstract Background Prefrontal repetitive transcranial magnetic stimulation (rTMS) has been used to induce side-specific mood changes in volunteers and patients. To clarify inconsistencies between reports that used different stimulation frequencies, we conducted a controlled study with a low (1 Hz) frequency, comparing left with right-sided stimulation Methods Nineteen healthy volunteers received randomised left or right prefrontal rTMS at a frequency of 1 Hz and 100% of motor threshold in two sessions two weeks apart. Results There were significant improvements with TMS for performance in the digit symbol substitution and verbal fluency tests, but no change of mood on a number of measures. There was also a reduction of pulse rate after TMS. The only side-specific TMS-effect was on mean arterial pressure, which decreased pressure after left, but not after right prefrontal TMS. Conclusions Apart from the unexpected and so far unreplicated effect on mean arterial pressure, there were no side-specific effects on mood in volunteers. It is unlikely that a simple laterality model of mood together with the assumed activating effect of higher and 'quenching' effect of lower stimulation frequency can account for the effects of TMS on mood.